Software innovations in clinical drug development and safety - Chakraborty, Partha, 1972-; Nagal, Amit, 1979- (Advances in medical technologies and clinical practice book series., 2016)
"This book is a comprehensive resource analyzing the integration of software engineering for the purpose of drug discovery, clinical trials, genomics, and drug safety testing"--Provided by publisher.